2011
DOI: 10.1111/j.1365-2745.2011.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent effects of habitat quality and climate on population growth of an endangered plant

Abstract: Summary 1.To predict the viability of populations, it is essential to clarify how performance depends both on large-scale environmental changes, such as climate warming, and on the local habitat. However, in spite of their potential importance, effects of interactions between large-scale environmental changes and the local environment on population viability have rarely been examined. 2. We investigated how population dynamics of the endangered alpine plant Dracocephalum austriacum depend on local habitat qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 43 publications
4
88
2
Order By: Relevance
“…In contrast to some studies reporting both negative and positive effects of climate change 444 on vital rates (Meer et al, 2016;Meisner et al, 2014;Nicolè et al, 2011), our study documents a 445 consistent negative effect of increased temperature and drought on lower-level vital rates in C.…”
contrasting
confidence: 91%
See 3 more Smart Citations
“…In contrast to some studies reporting both negative and positive effects of climate change 444 on vital rates (Meer et al, 2016;Meisner et al, 2014;Nicolè et al, 2011), our study documents a 445 consistent negative effect of increased temperature and drought on lower-level vital rates in C.…”
contrasting
confidence: 91%
“…In contrast, several studies 46 have documented negative effects of summer temperature on growth rates for other plant species (Aragón-Gastélum et al, 2017;Riba et al, 2002;Shryock et al, 2014). In some cases, a given 48 climatic variable has been shown to have diverging effects on separate vital rates within a species 49 life-history (Csergő et al, 2017;Jolls et al, 2015;Nicolè et al, 2011;Peñuelas et al, 2004;50 Treurnicht et al, 2016). For example, a warm summer increased the flowering probability of 51 Dracocephalum austriacum, whereas it decreased plant survival, leading to reduced effects of 52 climate on population growth rates (Nicolè et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These negative and hump shaped relationships to maximum temperature were unexpected since the ranges of H. nobilis and C. majalis extend as far as the Mediterranean Sea (Anderberg and Anderberg, 2015) where both annual and summer maximum temperatures are expected to be much higher than in Sweden. It has been argued that the effect of summer maximum temperatures may be indicative of species responses to summer drought (Ashcroft et al, 2008;Nicolè et al, 2011) as it has been reported that maximum temperature is a better predictor of soil moisture than Topographic Wetness Index (our proxy for soil moisture) during dry periods (Lookingbill and Urban, 2004). Similarly, we cannot exclude the possibility that the negative effects of maximum temperature on H. nobilis and C. majalis were caused by lower soil moisture at the warmer sites, especially in the absence of onsite measurements of soil moisture in the analyses.…”
Section: Landscape Physiography Microclimate and Species Distributionsmentioning
confidence: 99%